Measurement of dust emission from a road construction using exposure-profiling method - Jia, Qi; Al-Ansari, Nadhir; Knutsson, Sven (Natural Science, 2013)
Road construction is one example of heavy constructions that may have a substantial temporary impact on local air quality. Construction of Luleå Road during the summer 2013 generated a great deal of dust emission. US EPA recommended exposure-profiling method was used to measure dust emission. Inexpensive BSNE dust samplers were used instead of high volume samplers. The objective was to give a general idea of the amount of dust generated due to the construction work. Dust generation related to weather was discussed conditions. Estimated threshold wind velocity for road surface materials at the height of 2m were 12.88m/s, 12.88m/s and 24.76m/s which were lower measured wind velocity, indicated no dust generated from wind erosion. Dust masses for 7 sampling periods show dust generation had a close relation with moisture content of surface material. Wind speed, humidity had minor or no effect. The estimated dust emission rate in the construction work during the measuring period was 22.86kg TSP/d, 6kg/d was from construction work and 16.86kg/d was generated due to traffic on temporary roads. Godkänd; 2013; 20131128 (nadhir)